A legal evaluation of the impacts of developmental projects on biodiversity conservation in Nigeria - Onyenajua, Coleman Thompson (African journal of law and criminology, 2023)
The exodus of most rural dwellers, especially, in developing nations of the world, from the rural suburbs to the urban areas in the quest for greener pastures has brought about massive deforestation and uneven balance of natural resources in such countries. This, couple with a lot of projects by both government and companies affect the survival of plants and animals all over the world. Government most times site projects in areas endowed with forest without regards to the benefits of the forest to man and the entire environment. This is done with flagrant disregard to existing international, regional, and local laws on Biodiversity Conservation, which are meant to be obeyed and implemented to conserve ecological use of biodiversity on planet earth. To this effect, cross-sectional cooperation in all activities involving land ought to be encouraged if man should continue to survive. This paper seeks to x-ray the challenges, causes and laws in existence to conserve the use of land and biodiversity with particular focus on Nigeria. It also seeks non-legal ways to adequately tackle the menace and save the country’s natural heritage. Certain recommendations were made which includes the fact that only professionals should be allowed into policy making on biodiversity.